2015
DOI: 10.1002/mus.24755
|View full text |Cite
|
Sign up to set email alerts
|

In vivo treatment with the NF‐κB inhibitor ursodeoxycholic acid (UDCA) improves tension development in the isolated mdx costal diaphragm

Abstract: Because UDCA is used in treating certain clinical disorders, these results provide a rationale for human clinical trials using this and related drugs for treatment of Duchenne and related muscular dystrophies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…More specific targeting of immune and/or stress factors may provide novel therapeutic strategies with fewer side‐effects. Indeed, inhibitors of NFκB have shown promise in improving mdx muscle pathology such as a recent study which revealed improvements in mdx diaphragm force following NFκB inhibition with ursodeoxycholic acid . The pro‐inflammatory cytokine IL‐6, involved in skeletal muscle metabolism and maintenance and remodeling of myocytes, as well as regeneration after exercise and damage, is reported to be elevated in mdx tissue …”
Section: Discussionmentioning
confidence: 99%
“…More specific targeting of immune and/or stress factors may provide novel therapeutic strategies with fewer side‐effects. Indeed, inhibitors of NFκB have shown promise in improving mdx muscle pathology such as a recent study which revealed improvements in mdx diaphragm force following NFκB inhibition with ursodeoxycholic acid . The pro‐inflammatory cytokine IL‐6, involved in skeletal muscle metabolism and maintenance and remodeling of myocytes, as well as regeneration after exercise and damage, is reported to be elevated in mdx tissue …”
Section: Discussionmentioning
confidence: 99%
“…UDCA has been reported to benefit skeletal muscle in chronic inflammatory models such as mdx mice. Specifically, this effect of UDCA is associated with NF-κB-dependent transcriptional repression [ 79 81 ]. The present study demonstrated that UDCA induced sarcopenia in adult mice and sarcopenic-like effects in skeletal muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…C57BL/6J WT male mice (20–24 weeks old) were used in a randomized block experimental design. Each experimental group contained five to six mice and was treated with 200 mg/kg UDCA (Sigma-Aldrich, St. Louis, MO, USA) or vehicle (1.02% NaCl, pH 8.4) intragastrically for 6 weeks [ 81 ]. Male mice were chosen to avoid hormonal changes by reproductive cycles present in the female mice, which could affect muscle mass.…”
Section: Methodsmentioning
confidence: 99%